Deciphering changes in the incidence of the Guillain-Barré syndrome during the COVID-19 pandemic: a nationwide time-series correlation study - Hyunju Lee; Namwoo Heo; Donghyok Kwon; Jongmok Ha (BMJ Neurology Open, 2022)
Background Postinfectious autoimmunity is a hallmark of Guillain-Barré syndrome (GBS), and GBS incidence closely parallels that of its immune triggers. Sociobehavioural interventions implemented during the COVID-19 pandemic have altered the infectious disease landscape.Methods This nationwide time-series correlation study analysed GBS incidence, sentinel surveillance and SARS-CoV-2 vaccination data from January 2017 to December 2021 in the National Health Insurance Service and Korean Disease Control and Prevention Agency databases. The incidence of GBS and sentinel gastrointestinal and respiratory infectious diseases during the pandemic (2020–2021) was estimated and compared with both prepandemic (2017–2019) and incidence predicted in a time-series forecasting model. Time-series correlation analysis was used to examine the temporal association between GBS, infectious triggers and SARS-CoV-2 vaccination.Results During the pandemic, the total crude cumulative incidence rate was 2.1 per 100 000 population, which is lower than the prepandemic incidence, especially in age groups of less than 60 years. Seasonality was briefly interrupted during the winter of 2021. The majority of respiratory and some gastrointestinal conditions had a lower-than-expected incidence during the pandemic. Compared with the prepandemic state, during the pandemic period a higher number of gastrointestinal pathogens (Escherichia coli, Campylobacter spp., Clostridium perfringens, Yersinia enterocolitica and enteric adenovirus) had significant, moderate-to-strong positive temporal associations with GBS. The temporal association between SARS-CoV-2 infection and GBS was not significant, but SARS-CoV-2 vaccination exhibited a strong positive temporal association with GBS in 2021.Conclusion The incidence of GBS and sentinel infectious diseases decreased to below-expected levels during the pandemic, with the former attributable to the decreased incidence of non-COVID-19 respiratory and gastrointestinal infections. The evolving incidence of autoimmune postinfectious phenomena following the pandemic needs attention.